Change of Trilingual National Schools to Cooperative Education Unit Schools (SPK) Impact of Permendikbud No. 31 of 2014 - Kusmayanti, Shanti (Green Publisher Indonesia, 2025)
The term 3 Language National School has been known in Indonesia since the reform era. It is called the Three Language National School because this school includes Mandarin as a subject in addition to Indonesian and English. The government considers Mandarin to be a form of foreign cooperation. As a result, three Language Schools in Indonesia are included in the Cooperative Education Unit School or SPK. The term SPK, mentioned before Permendikbud No. 31/2014 regarding Cooperative Education Unit Schools, was previously referred to as International Schools. The purpose of this study is to analyze Permendikbud No. 31/2014, which changed the 3 Language National School to the Cooperative Education Unit School (SPK). The method used in this study is normative legal research using three approaches, namely the statutory approach, the case approach, and the conceptual approach. The essay will be conducted with analysis using a critical legal perspective and John Rawls' theory of justice. The study results reveal many problems stemming from the implementation of Permendikbud No. 31/2014. This has led to the decline of 3 Language Schools and has forced the 3 Language National Schools, which have a history and vision of being national schools, to also face challenges. Some of these schools are even at risk of dissolution.